GOLD-BEARING MINERALIZED ZONES OF THE YUZHNOE ORE OCCURRENCE AND ITS COMPARISON WITH LODE GOLD DEPOSITS OF YENISEI RIDGE - R Kh Mansurov (RUDN Journal of Engineering Research, 2016)
The relevance of the discussed issue is caused by the need to detect a new gold ore deposits within the Yenisei ridge to replenish the mineral resources of gold ore in Russia. The main aim of the study is to explore the features of geological structure and gold ore mineralized zones of ore occurrence Yuzhnoe in order to forecast gold ore bodies, and to substantiate the continuation of geological exploration. The prospecting is realized by the express method of prospecting of gold ore deposits in difficult mountain-taiga landscapes using a complex of lithogeochemical sampling for secondary dispersion halos, schlich, point and trench sampling; spectrochemical analysis for determination of gold content, ICP-MS, atomic-and-absorption, X-ray phase analysis and isotope-geochemical methods are used. The complex of prospecting methods allowed to reveal the ore-controlling zone of fold-discontinuous deformations and localize within it the ore occurrence Yuzhnoe. This ore occurrence is located at the south-eastern part of the Sredne-Ishimbinskaya area in the zone of dynamic influence of Ishimbinskiy deep fault system. The gold ore mineralized zones are revealed within the ore occurrence. They are presented by a series of lode gold stockwork subparallel bedding zones with low average gold content. A detection of gold ore bodies is forecasted within the most wide and lengthy zone Central`naya. Continuation of geological exploration is recommended. A comparison of the ore occurrence with model objects is carried out. A set of common criteria and indicators of ore occurrence with lode gold-sulfide deposits of the Yenisei ridge - Olimpiadninskoye, Veduginskoye, etc. and with «carlin» type deposits is established. For the first time in the region the gold ore mineralized zones in carbonate-terrigenous carbonaceous sediments of kartochki and aladyinskaya series of the Middle Riphean are detected. Perspectives of gold-bearing mineralization of the eastern slope of the Yenisei ridge are defined.